THE ROLE OF DIGITAL PLATFORMS IN ENHANCING PHYSICS EDUCATION - Pardayeva Kibriyo Zafar qizi (Bright Mind Publishing, 2025)
This article explores the integration of digital tools in physics education, emphasizing their transformative impact on teaching and learning. It highlights the benefits of interactive simulations, virtual laboratories, and online resources in facilitating the visualization of abstract concepts, promoting collaboration, and expanding access to educational materials. The discussion includes prominent examples such as PhET Interactive Simulations, Khan Academy, and MIT Open Course Ware, illustrating how these platforms support constructivist learning approaches. The paper also addresses challenges, notably the digital divide and the necessity of maintaining the educator’s role in technology-enhanced environments. Looking forward, the article anticipates advancements through artificial intelligence, adaptive learning systems, and immersive technologies like virtual and augmented reality. These innovations are expected to further personalize and deepen physics learning, provided that equitable access and teacher training are ensured.
Keywords: Digital tools, physics education, interactive simulations, virtual laboratories, online learning platforms, collaborative learning, educational technology, digital divide, artificial intelligence, virtual reality, augmented reality, constructivist learning.